ANALISIS KESULITAN PENULISAN HANZI PADA SISWA KELAS VI SD ZION GKKA-UP MAKASSAR DALAM PEMBELAJARAN BAHASA MANDARIN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and analyze the difficulties experienced by students in writing Hanzi. The method used is a quantitative descriptive approach, with data collected through writing tests and questionnaires distributed to students of SD Zion GKKA-UP Makassar who are learning Mandarin.The results of the study reveal that students still face various challenges, with stroke order being the most dominant difficulty (100%). This is followed by difficulties in maintaining proportion and character structure (86.7%), neatness of writing (60.0%), and distinguishing characters with similar forms (40.0%).The factors influencing these difficulties include a lack of practice time and variation in teaching methods (100%), unfamiliarity with strict writing rules (66.7%), as well as students’ perceptions of the potential of digital media in increasing learning motivation (86.7%).